ANALISA DINAMIKA FAKTOR-FAKTOR PENENTU INDEKS PEMBANGUNAN MANUSIA : PERSPEKTIF KEBERLANJUTAN DAN KESEJAHTERAAN: ANALISA DINAMIKA FAKTOR-FAKTOR PENENTU INDEKS PEMBANGUNAN MANUSIA : PERSPEKTIF KEBERLANJUTAN DAN KESEJAHTERAAN - Wina Paul; Ikhsan Nuralam (AL-INTIFA, 2024)
This research aims to analyze the dynamics of the determining factors of the Human Development Index (HDI) from a sustainability and welfare perspective. This approach involves an in-depth study of the various factors that influence HDI, with a focus on economic, social and environmental aspects. This research methodology includes current statistical data analysis, regression models, and system dynamics modeling techniques. The results illustrate how changes in factors such as per capita income, access to education, and public health can influence changes in HDI over time. Sustainability analysis focuses on the long-term impact of development policies and actions on the welfare of society and the environment. The findings of this research provide in-depth insight into how complex interactions between economic, social and environmental factors can influence the achievement of sustainable human development goals. The implications of this research can be the basis for formulating more holistic and sustainable development policies, taking into account important aspects that influence human welfare in the long term. Keywords: HDI, Sustainability, community welfare